Foreign Valuta (In the Perspective of Islamic Economics) - Hannanong, Ismail; Bin Sapa, Nasrullah; Wijaya, Abdi; Nur Haslin, Muh Ilham (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
The purpose of this study is to determine and analyze the views of Islamic economic law on foreign exchange (Al-Sharf), which is one of the transaction tools to meet basic human needs throughout the world today. Forex transactions are very common in the community. This forex transaction is motivated by basic needs when transacting across countries or in other countries. This research uses a qualitative method using a literature study to find out the Islamic view of foreign exchange. There are several types of forex / sharf buying and selling schemes encountered such as spot, forward, swap and option but it is still necessary to know which ones are allowed in the Sharia economic system and which ones are not allowed and the reasons through reading literature, books and documents that discuss foreign exchange trading, as well as reviewing and analyzing them from the perspective of Islamic economic law.